Penyuluhan Demam Berdarah Dengue (DBD) Kepada Pelajar-Pelajar Di Perguruan Kristen Methodist-2 Rantauprapat - Saharnauli Janna Verawaty Simorangkir (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
Coronaviruses are a large family of viruses that cause illness ranging from mild to severe symptoms. The increase in the number of COVID-19 cases is happening fast enough and there has been a spread between countries. Based on scientific evidence, COVID-19 can be transmitted from human to human through droplets, not through the air. Standard recommendations for preventing the spread of infection are regular hand washing with soap and clean water, practicing coughing and sneezing, avoiding direct contact with livestock and wild animals and avoiding close contact with anyone showing symptoms of respiratory illness such as coughing and sneezing. This community service is in the form of counseling that aims to provide correct information and knowledge about COVID-19, its transmission and prevention to students at Santa Maria Medan Private High School so it is hoped that it will help in breaking the chain of COVID-19 transmission which is increasingly rampant.